Synthesis, Characterization and Cytotoxicity of (?6-p-cymene)ruthenium(II) Complexes of ?-Amino Acids - Egbewande, Folake A.; Paul, Lydia E. H.; Therrien, Bruno; Furrer, Julien (My University, 2014)
Arene ruthenium complexes of ?-amino acids, obtained by mixing aq. solns. of [(?6-p-cymene)RuCl2]2 in the presence of AgCF3SO3 with various amino acids, have been studied at 37 °C using NMR spectroscopy and electrospray ionization mass spectrometry (ESI-MS). Small hydrophobic ?-amino acid anions were found to form bidentate N,O-chelate complexes, whereas ?-amino acids with coordinating side chains (e.g. serine, aspartic acid, histidine) acted as tridentate ligands. For many amino acids, more than two chelate complexes were formed. Presumably, complexes with the general formula [(?6-p-cymene)Ru(AA)2]n+ and bridged complexes with the general formula [{(?6-p-cymene)Ru}2(?-AA)2(?-OH)]+ were obsd. together with the expected bi- and tridentate chelate complexes. All complexes, isolated as triflate salts, were evaluated for their in vitro anticancer activity against the human ovarian cancer cell line A2780 and its cisplatin-resistant mutant A2780cisR. All complexes were found to be highly cytotoxic, with IC50 values ranging from 0.16-19.8 ?M. Interestingly, all complexes were selectivity active against A2780 cells relative to the A2780cisR variants, indicating a distinct mechanism of action that differs from that of many previously reported cytotoxic ruthenium complexes. No direct correlation between the kinetics of complex formation and cytotoxicity was apparent, suggesting that other physicochem. parameters such as complex stability and ligand exchange kinetics may play important roles in the biol. activity. [on SciFinder(R)]